Atitudes dos estudantes de medicina a respeito da relação médico-paciente - Pereira, Cláudia Maria Alves da Silva (2017)
Introduction: Medical schools are engaged in curricular reforms that have among their purposes the implementation of a more patient-centered care and relationship-centered professional values. Despite efforts for curricular changes, desirable outcomes towards medical education have not been fully achieved. Objectives: To assess medical students’ attitudes towards the doctor-patient relationship and to determine predictors of medical students’ patient-centered attitudes among different curricular designs. Material and methods: Cross-sectional study (August 2015 to March 2016) that assessed medical students’ attitudes from 1st to 6th year of 21 Brazilian medical schools participating in the project for evaluation of change trends proposed by the Evaluation Commission of Health Schools of the Brazilian Association of Medical Education (21/46, 45.6%). Participating schools are engaged in different stages of curricular designs (traditional, innovative and advanced). Students completed a questionnaire with sociodemographic and curricular characteristics and the Brazilian version of the Patient-Practitioner Orientation Scale (B-PPOS) through an online website-platform. Results: Most of medical students were female (59.3%; n=867), with a mean age of 22.3 (SD=3.3) years, enrolled at a public school (87.9%; n=1,286). Of all students, 30.6% (n=448) were enrolled in advanced curricular designs, 24.3% (n=355) reported having communication-skills activities in the curriculum and 48.9% (n=715) had participated in extracurricular activities. Medical students were moderately patient-centered, with higher caring than sharing scores throughout all years of medical training (p<0.001; =0.599). There was no statistical difference among total, sharing and caring scores according to different curricular designs (p>0.05), except in caring subscale related to the psychosocial context, in which students enrolled in traditional and innovative curricula had lower scores than those in advanced-curriculum schools (p=0.000; =0.111and =0.134, respectively). Female students were more patient centered than men in total, sharing, caring domains and subscales scores (p<0.001; 0.136≤≤0.305), except in 5th and 6th years. Female gender (B=0.180; 95%CI=0.13, 0.23; p<0.001), students enrolled in public schools (B=0.132; 95%CI=0.06, 0.21; p<0.001), year of medical training (B=0.021; 95%CI=0.00, 0.04; p=0.019), preference for future medical practice in public services (B=0.053; 95%CI=0.03, 0.08; p<0.001) and extracurricular activities (B=0.068; 95%CI=0.02, 0.12; p=0.008) were predictors of patient-centered attitudes among medical students. Students enrolled in schools with communication skills activities in the curriculum were more likely to ask questions about patients’ background (OR=4.53; 95%CI=1.02, 20.15) and to let patients ask questions about their condition (OR=1.46; 95%CI=1.09, 1.95). Conclusion: Medical students are moderately patient-centered. Curricular design does not predict medical students’ attitudes. Being female, going to a public medical school and having communication skills activities in the curricular syllabus are important predictors of patient-centered attitudes among medical students.